Effect of concurrent training on physical performance and quality of life in children with malignancy: A systematic review and meta-analysis - Zang, Wanli; Fang, Mingqing; Chen, Haohao; Huang, Xinmeng; Li, Dong; Yan, Jin; Shu, Heng; Zhao, Mingyuan (Frontiers in Public Health, 2023)
Objective This study aims to evaluate the intervention effect of concurrent training on children with malignant tumors to provide evidence for prescribing exercise for children with malignant tumors. Methods Twelve databases were searched from inception to October 15, 2022. Two researchers independently screened the literature, evaluated the quality, extracted the data, and performed the meta-analysis using R. Result A total of nine randomized controlled trials involving 371 children were included in this study. The meta-analysis revealed that muscle strength was significantly greater in the exercise group compared to the usual care group [SMD = 0.26, 95% CI (0.04, 0.48), P = 0.023], with subgroup analysis showing no significant difference in upper limb [SMD = 0.13, 95% CI (−0.17, 0.43), P = 0.318] and a considerable difference in lower limb strength [SMD = 0.41, 95% CI (0.08, 0.74), P = 0.015]. Physical activity [SMD = 0.57, 95% CI (0.03, 1.1), P = 0.038], timed up and down stairs test [SMD = −1.22, 95% CI (−2.04, −0.4), P = 0.004], 6-min walking ability [SMD = 0.75, 95% CI (0.38, 1.11), P < 0.01], quality of life [SMD = 0.28, 95% CI (0.02, 0.53), P = 0.033], and cancer-related fatigue [SMD = −0.53, 95% CI (−0.86, −0.19), P = 0.002] were significantly better than the usual care group. There were no significant differences in peak oxygen uptake [SMD = 0.13, 95% CI (−0.18, 0.44), P = 0.397], depression [SMD = 0.06, 95% CI (−0.38, 0.5), P = 0.791], and withdrawal rates [RR = 0.59, 95% CI (0.21, 1.63), P = 0.308] between the two groups. Conclusion Concurrent training could improve physical performance for children with malignancy but had no significant effect on mental health. Because the quality level of evidence is mostly very low, future high-quality randomized controlled trials are required to confirm these findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=364140, identifier CRD42022308176.